2017
DOI: 10.1071/py15191
|View full text |Cite
|
Sign up to set email alerts
|

Findings from a clinical audit in regional general practice of management of patients following acute coronary syndrome

Abstract: Patients with acute coronary syndrome (ACS) require ongoing treatment and support from their primary care provider to modify cardiovascular risk factors (including diet, exercise and mood), to receive evidence-based pharmacotherapies and be properly monitored and to ensure their take-up and completion of cardiac rehabilitation (CR). This study assesses adherence to National Heart Foundation guidelines for ACS in primary care in a regional centre in Western Australia. Patients discharged from hospital after a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…Клинические аудиты часто проводятся не только в стационарах, но также и в сфере деятельности врачей общей практики и в амбулаторных учреждениях [26].…”
Section: терминологияunclassified
“…Клинические аудиты часто проводятся не только в стационарах, но также и в сфере деятельности врачей общей практики и в амбулаторных учреждениях [26].…”
Section: терминологияunclassified
“…[8][9][10] However, there can be a gap of weeks to months between hospital discharge and commencement of outpatient (phase 2) cardiac rehabilitation. 11 This gap has led to calls for a more seamless transition between hospital discharge and phase 2 cardiac rehabilitation. 12 In addition, a variety of both programrelated and person-related factors means that access to and uptake of cardiac rehabilitation is limited.…”
Section: Introductionmentioning
confidence: 99%
“…A previous systematic review identified 11 studies that had explored ways to facilitate physical activity engagement during the first few months following CABG surgery outside of the supervised cardiac rehabilitation setting. 14 Strategies identified in this review that are shown to increase physical activity levels post-CABG surgery were as follows: the provision of written information, 15 verbal information provided by health professionals, 16 one-onone peer support, 17 and videos modeling other patients coping with challenges.…”
Section: Introductionmentioning
confidence: 99%